Analisis Kemampuan Penalaran Matematis pada Materi Sistem Persamaan Linear Dua Variabel untuk Siswa Kelas VIII B SMP Negeri 6 Kodi - Inna, Maya Tamo; Lede, Yulius Keremata; Making, Samuel Rex Muliyadi; Lubur, Dorothea Novia Ludo (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to determine the mathematical reasoning abilities of students in solving problems on the topic of Systems Of Linear Equations In Two Variables at SMP Negeri 6 Kodi. The type of this research is qualitative research. The subjects of this research are all the students of class VIII B at SMP Negeri 6 Kodi, totaling 29 students. The interview subjects were three students from each category, namely the high, medium, and low categories. The object of this research is for the researcher to understand the mathematical reasoning abilities of the students. The data collection techniques used are written tests, interviews, and documentation. Based on the reserch results, the mathematical reasoning ability on the topic of systems of two variable linear equations (SPLDV) for students in class VIII B SMP Negeri 6 Kodi shows variation in meeting the reasoning indicators. Students with high mathematical reasoning ability are able to meet for mathematical reasoning indicators in solving SPLDV problems. Students with moderate mathematical reasoning ability can meet three indicators, while students with low mathematical reasoning ability can only meet one reasoning indicator in solving SPLDV problems. So, the researcher can conclude that the mathematical reasoning ability of the eighth-grade students of SMP Negeri 6 Kodi is still very low